The endophytic fungus Penicillium oxalicum isolated from Ligusticum chuanxiong Hort possesses DNA damage-protecting potential and increases stress resistance properties in Caenorhabditis elegans - Zizhong Tang; Yihan Qin; Yueyu Wang; Wenjie Lin; Qing Wang; Nayu Shen; Yirong Xiao; Hong Chen; Hui Chen; Tongliang Bu; Qingfeng Li; Huipeng Yao; et al. (Frontiers Media S.A., 2022)
The chemical composition and antioxidant activity of extracts (POE) of Penicillium oxalate isolated from Ligusticum chuanxiong Hort have been investigated. However, the biological activity of POE is limited, and its antioxidant, stress resistance and DNA protection effects in vivo are unclear. The current study aims to explore the beneficial effects of POE on DNA damage protection in pBR322 plasmid and lymphocytes and stress resistance in Caenorhabditis elegans. The results showed that POE increased the survival rate of C. elegans under 35°C, UV and H2O2 stress, attenuated ROS and MDA accumulation, and enhanced the activity of some important enzymes (SOD, CTA, and GSH-PX). In addition, the POE-mediated stress resistance involved the upregulation of the expression of the sod-3, sod-5, gst-4, ctl-1, ctl-2, daf-16, hsp-16.1, hsp-16.2, and hsf-1 genes and acted dependently on daf-16 and hsf-1 rather than skn-1. Moreover, POE also reduced lipofuscin levels, but did not prolong the lifespan or damage the growth, reproduction and locomotion of C. elegans. Furthermore, POE showed a protective effect against DNA scission in the pBR322 plasmid and lymphocytes. These results suggested that P. oxalate extracts have significant anti-stress and DNA protection potential and could be potential drug candidates in the pharmaceutical field, thus greatly broadening the understanding of the biological effects of the endophytic fungus P. oxalate.